Process simulation and energy optimization for the pulp and paper mill - Ji, Xiaoyan; Lundgren, Joakim; Wang, Chuan; Dahl, Jan; Grip, Carl-Erik (Luleå tekniska universitet, Energivetenskap, 2010)
A process integration model is developed based on mixed integer linear programming. The analysis is carried out using the reMIND software in combination with the commercial optimization software CPLEX. The steam production (heat recovery boiler, bark boiler and steam turbines) and the process steam consumers (digester, evaporation plant, bleaching plant as well as pulp dry machine and paper making machine) are modeled as separate modules and thereafter linked and are validated using the operation data from a pulp and paper mill in the Northern Sweden. The whole plant is simulated and initial optimization runs are performed in which the cost is to be minimized. Validerad; 2011; 20101206 (xiajix)